English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

If given
f(x) = 4x to the 2nd power -x -4
(4^2-x-4)

Find f(x +2)?

If anyone knows it'll be really heplful

2006-10-22 17:07:06 · 6 answers · asked by Taylor made 2 in Science & Mathematics Mathematics

6 answers

You can just replace x with x+2.

So, with f(x) = (4x^2-x-4), then
f(x+2) = [4(x+2)^2-(x+2)-4]
=4(x^2+4x+4) - x - 2 - 4
=4x^2+16x+16 - x - 2 - 4
=4x^2+15x+10


That's assuming you mean 4x^2 and not (4x)^2.

2006-10-22 17:08:53 · answer #1 · answered by Rev Kev 5 · 1 0

F(x+2) = 4(x+2)^2-(x+2)-4
=4(x^2+4x+4)-x-2-4
=4x^2+16x+16-x-6
=4x^2+15x+10

Wal C .. check your distribution....Rev, i would say the same to you, but i see you noticed your mistake and fixed it.

2006-10-23 00:15:10 · answer #2 · answered by JLEETZ 2 · 0 0

f(x) = 4x² - x - 4
So f(x + 2) = 4(x + 2)² - (x + 2) - 4
= 4(x² + 4x + 4) - x - 2 - 4
= 4x² + 16x + 4 - x - 6
= 4x² + 15x - 2

2006-10-23 00:13:52 · answer #3 · answered by Wal C 6 · 0 0

f(x) = 4x^2 - x - 4
f(x+2) = 4(x+2)^2 - (x+2) - 4
f(x+2) = 4(x^2 + 4x + 4) - x - 2 - 4
f(x+2) = 4x^2 + 16x + 16 - x - 6
f(x+2) = 4x^2 + 15x + 10

2006-10-23 00:19:27 · answer #4 · answered by Helmut 7 · 0 0

in your original equation substitute y for x.
f(y) = 4*y^2 - y - 4

now let y = x + 2

f(y) = 4* (x+2) ^2 - (x + 2) -4

now simplify.

I find that making a substitution of variables as the first step helps me to not get confused.

2006-10-23 00:20:52 · answer #5 · answered by Curly 6 · 0 0

I agree with JEELTZ

2006-10-23 00:16:57 · answer #6 · answered by palmerdrury 1 · 0 1

fedest.com, questions and answers